Clinical features of macrocephaly at birth in Korea - Goun Jeong; Minkyun Kim; Byoung Hee Han (Korean Pediatric Society, 2014)
PurposeThis study aimed to investigate the clinical features of macrocephaly at birth in Korea using ultrasonography.MethodsWe retrospectively investigated the medical records of full-term birth neonates in Cheil General Hospital & Women's Healthcare Center from January 2000 to June 2012. The following parameters were recorded and analyzed: gestational age, sex, birth weight, height, occipitofrontal circumference (OFC), physical examination, perinatal problems, and ultrasonography results. Macrocephaly was diagnosed when the OFC was greater than two standard deviations, based on the 2007 Korean National Growth Charts.ResultsThere were 75 neonates with macrocephaly at birth (52 boys and 23 girls), with a mean OFC of 38.1±0.49 cm. A comparison of the birth weight and height with the OFC value showed that height was correlated with OFC (r=0.35) but birth weight was not correlated with OFC (r=0.06). There were no remarkable findings in 56 cases (75%). Germinal matrix hemorrhage was identified in 10 cases (13%). An enlarged cerebrospinal fluid space was found in 5 cases (6.7%). There were 3 cases of mega-cisterna magna (4%), 1 case of ventriculomegaly, and 1 case of an enlarged interhemispheric space (6 mm) among these patients. In addition, a choroid plexus cyst was seen in 1 case. Mineralizing vasculopathy in both basal ganglia with no evidence of congenital infection was found in 2 cases and an asymptomatic subarachnoid hemorrhage was found in 1 case.ConclusionOur results indicate that macrocephaly at birth has benign ultrasonography findings and shows a pattern of male dominance.